Perbandingan Penyimpangan Prinsip Kesopanan Budaya India dan Perancis Dalam Film The Hundred-Foot Journey - Santosa, Marisa Puteri Sekar Ayu (sarasvati, 2020)
This study aims to investigate the comparison of the deviations of the principle of politeness in Indian and French culture in a film called The Hundred-Foot Journey. Here the author uses Leech's theory of politeness principles which consists of maxims: (1) maxim of wisdom, (2) maxim of generosity, (3) maxim of praise, (4) maxim of humility, (5) maxim of compatibility, and (6) maxim of sympathy. Of these 2 cultures, only 3 maxims deviations were found consisting of: (1) deviations of wisdom maxims, (2) deviations of humility maxims, and (3) deviations of the maxims of agreement. The most common deviations in the principle of politeness in these two different cultures are maxim of agreement. The culture that often violates the maxim of agreement is Indian culture, which commits 16 violations, while France has 11 violations.